ESTIMATING FLOW CHARACTERISTICS OF DIFFERENT WEIR TYPES AND OPTIMUM DIMENSIONS OF DOWNSTREAM RECEIVING POOL - Emiroglu, M. Emin (Veda, Slovak Acad Sciences, 2010)
This paper presents the results of a laboratory study on the flow characteristics of sharp-crested weirs, broad-crested weirs, and labyrinth weirs. The variation of the maximum bubble penetration depth for different weir types is investigated depending on overfall jet expansion, discharge, and drop height. Moreover, most efficient depth, length and width of the downstream receiving pool in an open channel system are studied by considering the penetration depth, overfall jet expansion, jet trajectory and the bubble zone. The results show that overfall jet expansion at the labyrinth weirs is significantly wider than the rectangular sharp-crested weirs and the trapezoidal sharp-crested weir. It is demonstrated that the labyrinth weirs have the lowest values of bubble penetration depth among the weirs tested. Furthermore, it is found that the rectangular and the trapezoidal weirs are observed to have the highest bubble penetration depth among all weirs. Consequently, empirical equations are obtained for predicting the maximum penetration depth of bubbles, trajectory of free overfall nappe, jet expansion of free overfall nappe, and the length of the bubble zone.
Ur?ovanie prúdov?ch charakteristík rozdielnych typov priepadov a optimálny návrh v?varu
Keywords: Weir; Penetration Depth; Jet Expansion; Jet Trajectory; Bubble; Air Entrainment; Aeration